Aqueous Photon Upconversion by Anionic Acceptors Self-Assembled on Cationic Bilayer Membranes with a Long Triplet Lifetime - Asthana, Deepak; Hisamitsu, Shota; Morikawa, Masa-aki; Duan, Pengfei; Nakashima, Takuya; Kawai, Tsuyoshi; Yanai, Nobuhiro; Kimizuka, Nobuo (Organic Materials, 2019)
Anionic 9,10-diphenylanthracene chromophores electrostatically bound to cationic, chiral bilayer membranes show ordered self-assembly in water. The integrity of the chromophore-accumulated aqueous bilayer membranes is ensured by multiple hydrogen-bond networks introduced in the bilayer, which allowed adaptive accommodation of the guest chromophores at the inner surface of the bilayer while maintaining their cohesive interactions. The regular chromophore alignment in the aqueous assembly is confirmed by differential scanning calorimetry, circular dichroism, and circularly polarized luminescence spectra. Excitonic migration of triplet energy occurs among the chromophores densely organized at the inner surface of the bilayer, which lead to triplet–triplet annihilation-based photon upconversion (TTA-UC). This acceptor-bilayer self-assemblies show a notably long triplet lifetime of 8.0 ms, which allows TTA-UC at sufficiently low excitation light intensity. These results demonstrate the usefulness of the simple electrostatic accumulation approach for TTA-UC chromophores where the suitable molecular design of the TTA-UC chromophore-integrated bilayer membranes plays a key role.
Keywords: self-assembly; photon upconversion; triplet; triplet–triplet annihilation; bilayer membranes; energy migration